Newspapers and public grants: A matter of quality. (1st November 2017) - Battaggion, Maria Rosa; Vaglio, Alessandro
Abstract: The present paper deals with the issue of newspaper subsidies in a framework of endogenous quality provision. We compare monopoly and duopoly cases in a vertically differentiated model. For monopolies we show that a per‐copy subsidy reduces quality. Conversely, in duopolies in the vertically differentiated model, we show that a state subsidy might increase the quality of the low‐quality newspaper and decrease the quality of the high‐quality newspaper.